Economic deprivation and intimate partner violence in Germany - Lara Minkus; Ruth Abramowski (PLoS ONE, 2025)
This article examines the association between economic deprivation and the likelihood of experiencing physical intimate partner violence (IPV) in Germany. Although international studies have shown a link between economic deprivation and IPV, analyses utilizing probability-based surveys to examine this association in Germany are scarce. Within the framework of an economic power resource approach and using the German Family Panel pairfam, a large probability-based panel, this study aims to fill this gap. Results of linear probability models show that being unemployed and being unsatisfied with the household finances, as indicators of economic deprivation, significantly increase the risk of physical IPV. A range of sensitivity checks corroborate these findings.